Studi Suhu Pengovenan terhadap Umur Simpan Telur Asin - D Novia; S Melia; N.Z Ayuza (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2012)
This study aims to determine the effect of oven temperature on the moisture content, total bacterial colonies and shelf life of salted eggs. This study uses duck eggs coast (Indian Runner) maximum 48-hour-old fresh as many as 200 eggs weighing 65-70 grams obtained from a breeder in Anduring Padang. The research used the experimental method with randomized block design (RBD), consists of 4 treatments and 5 groups as replication. Treatment A (oven temperature 70oC), B (80oC), C (90oC) and D (100oC). Eggs were roasted in the oven for 6 hours after that eggs were stored for 25 days. Variables measured were moisture content, total bacterial colonies, and shelf life of salted eggs. The results showed significantly different effects (P<0.05) on moisture content and shelf life but showed non significant effects (P>0.05) on total bacterial colonies of salted eggs. Based on the results of this study, it can be concluded that the oven temperature of salted egg is best at 100oC with moisture content of 48.79%, total bacterial colonies 7.35 x 104 CFU/g, and 38.80 days shelf life.